Bioavailable and free 25-hydroxyvitamin D and vitamin D binding protein in polycystic ovary syndrome: Relationships with obesity and insulin resistance. Issue 177 (March 2018) - Naderpoor, Negar; Shorakae, Soulmaz; Abell, Sally K.; Mousa, Aya; Joham, Anju E.; Moran, Lisa J.; Stepto, Nigel K.; Spritzer, Poli Mara; Teede, Helena J.; de Courten, Barbora
Highlights: Serum vitamin D binding protein (DBP) concentrations were lower in women with PCOS compared to controls. DBP concentration was not related to BMI, adiposity or insulin resistance. High density lipoprotein (HDL) was inversely related to DBP and remained the main determinant of DBP concentration after adjusting for covariates. Bioavailable and free 25(OH)D concentrations were not different between women with and without PCOS. Abstract: Polycystic ovary syndrome (PCOS) is a common condition characterised by both reproductive and metabolic features (obesity, insulin resistance, diabetes risk). Some evidence suggests that women with PCOS have lower vitamin D levels compared to healthy controls. Vitamin D binding protein (DBP) is the main carrier of vitamin D in circulation and plays an important role in regulating vitamin D concentration and bioavailability for target tissues. To our knowledge, no previous studies have examined DBP, bioavailable and free 25-hydroxyvitamin D (25(OH)D) in women with PCOS. The primary aim of this study was to compare DBP, bioavailable and free 25(OH)D concentrations in women with PCOS and controls. The secondary aim was to investigate relationships between DBP, bioavailable and free 25(OH)D and metabolic features (anthropometric measures, insulin resistance, and lipid profile). In a cross sectional study using bio-banked samples, we measured 25(OH)D, DBP and albumin. Bioavailable and free 25(OH)D were calculated using previously validated formula. BMI, body composition (dual X-ray absorptiometry, DXA), insulin resistance (homeostatic model assessment of insulin resistance (HOMA-IR)) and glucose infusion rate (GIR) from hyperinsulinaemic euglycaemic clamp and serum lipids (ELISA) were also measured in a physically and biochemically well-characterised cohort of women with and without PCOS. We studied 90 women with PCOS and 59 controls aged 18–48 years. DBP concentrations were lower in PCOS compared to controls (median [IQR]: 443.40 [314.4] vs 482.4 [156.8] μg/ml, p = 0.02). No significant differences were found in bioavailable or free 25(OH)D concentrations between groups. DBP was not associated with BMI, percent body fat or markers of insulin resistance (all p > 0.2). High-density lipoprotein (HDL) was the main determinant of DBP in the overall cohort (β = −0.12, p = 0.02), after adjusting for covariates including PCOS/control status, age, BMI, total 25(OH)D and HOMA-IR. In PCOS, total and free 25(OH)D were related to markers of insulin resistance and lipids. Only the associations between free 25(OH)D and triglycerides (p = 0.02), and HDL (p = 0.03) remained significant after adjusting for age and BMI. In conclusion, women with PCOS had lower DBP, but similar bioavailable or free 25(OH)D concentrations compared to controls, independent of BMI and age. DBP was not associated with insulin resistance or BMI in PCOS. Further studies are needed to investigate the pathophysiology and clinical implications of reduced DBP in PCOS.